Smartphone addiction: relationship between gender, emotional instability and loneliness among UiTM Raub students / Suriyati Ujang ...[et al.] - Ujang, Suriyati; Md Yusof, Norhidayah; Maulad Mohamad Rawi, Intan Nadia Azvilla; Badrul Azhar, Badrina Nur Yasmin; Mohamad, Nur Ainin Sofea; Mohd Yusoff, Yati Najihah (2016)
This study was conducted to look in depth on smartphone addiction among UiTM Raub students. This is due to a situation where it can be seen that most of students always use the smartphones whenever and wherever they go. Furthermore, UiTM Raub has been provided with a full wifi-coverage, thus, the students have ready access to internet. Therefore, there are three objectives of this study which are 1) to find out the relationship between smartphone addiction and gender 2) to study the relationship between smartphone addiction and emotional instability (stress) and 3) to study the relationship between smartphone addiction and loneliness among students. The population of this study is 2835 students in UiTM Raub, Pahang. The sample for this study consists of 338 respondents. Furthermore, this study employed stratified sampling technique. The results that were obtained stated that;1) there is no a relationship between smartphone and gender 2) there is a relationship between smartphone addiction and emotional instability (stress) and 3) there is a relationship between smartphone addiction and loneliness. It can be concluded that the relationship between smartphone addiction and emotional instability (stress) and loneliness, all is significant. However, for relationship between smartphone and gender, there is no significant can be proven. Thus, further research could be carried out in order to track the students smartphone habit and to know the relaxation techniques when they are feeling stress and lonely.